The Effectiveness of the Stunting Prevention and Early Detection Module on Increasing Knowledge of Pregnant Women at the Mare Health Center - Mutmainnah Mutmainnah; Musni Musni; St. Malka (Journal La Medihealtico, 2022)
One indicator of the welfare of a nation can be seen from the human resources in the country, if human growth and development in a country is good, it will increase the productivity of human performance it self and will affect the welfare of the nation. Stunting is one of the nutritional problems that is currently in the spotlight because in additional to its impact on health, it also has an impact on socio-economic conditions. This research method is quantitative using Quasi Experiment (Pretest and posttest design). The sampling method in this study was purpossive sampling. The total sample in this study was 40 pregnant woman who were in the working area of the Mare Health Center. Data analysis using Wilcoxon test. Form the results of the Wilcoxon test analysis, it was found that the p value= 0.101 (p>0.05), which means that the stunting prevention and early detection module is not effective in increasing the knowledge of pregnant women in the working area of the Mare conditions.